The effects of endurance exercise in hypoxia on acid-base balance, potassium kinetics, and exogenous glucose oxidation - Sumi, D.; Kasai, N.; Ito, H.; Goto, K. (Frontiers in Physiology, 2019)
Purpose: To investigate the carbohydrate metabolism, acid-base balance, and potassium kinetics in response to exercise in moderate hypoxia among endurance athletes.